2013
DOI: 10.1093/petrology/egt066
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Origin and Evolution of Magmas in the Payún Matrú Volcanic Field, Quaternary Andean Back-arc of Western Argentina

Abstract: The Payu¤ n Matru¤ Volcanic Field (Pleistocene^Holocene) is located in the Andean back-arc of the Southern Volcanic Zone, western Argentina, and is contemporaneous with the Andean volcanic arc at the same latitude. It includes two polygenetic, mostly trachytic volcanoes: Payu¤ n Matru¤ (with a summit caldera 8 km wide) and Payu¤ n Liso (a smaller stratovolcano). The volcanic field includes about 200 scoria cones and alkali basaltic and trachybasaltic lava flows, forming two basaltic fields around Payu¤ n Matru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 64 publications
2
36
0
2
Order By: Relevance
“…These granites are petrographically similar to the xenolith observed in this study. We contaminate two primitive basalt compositions with lower and upper crustal contaminants: one from Davidson and de Silva [13] for basalts from the central Altiplano, and a second from Hernando et al [42] for pre-caldera basalts from the Payún Matrú volcanic field in western Argentina's Southern Volcanic Zone. Table 3 presents concentrations and isotopic ratios of the contaminants and basalts.…”
Section: Petrogenesis Of Cerro Uturuncu Magmasmentioning
confidence: 99%
“…These granites are petrographically similar to the xenolith observed in this study. We contaminate two primitive basalt compositions with lower and upper crustal contaminants: one from Davidson and de Silva [13] for basalts from the central Altiplano, and a second from Hernando et al [42] for pre-caldera basalts from the Payún Matrú volcanic field in western Argentina's Southern Volcanic Zone. Table 3 presents concentrations and isotopic ratios of the contaminants and basalts.…”
Section: Petrogenesis Of Cerro Uturuncu Magmasmentioning
confidence: 99%
“…In this regard, the required metasomatic agent would have higher Th, LREE and Hf contents than that proposed by experimental fluid/rock partition studies (e.g., Davidson et al, 2013;Johnson, 1998;Nelson and Davidson, 1993;Salters and Longhi, 1999). Numerous studies have shown that many geochemical features of arc-related rocks, such as enrichment in Hf isotopic composition or the depletion in Nb and Ta, can be attributed to slab-derived melts (e.g., Hernando et al, 2014;Pearce and Stern, 2006;Shao et al, 2014). In combination with geochemical and petrological features of the Liuluocun volcanic rocks, especially they show different characteristics of trace elements (Fig.…”
Section: Petrogenesis Of the Liuluocun Volcanic Rocksmentioning
confidence: 96%
“…This is clearly indicated by the petrology and geochemistry of magmas from monogenetic eruptions, which evidence certain degree of differentiation in most cases and occasional assimilation of crustal rocks that occurred at different depths (Thirlwall et al, 2000;Klügel et al, 2005;Stroncik et al, 2009;Valentine and Hirano, 2010;Brenna et al, 2011;Rowe et al, 2011;Hernando et al, 2014;Albert et al, 2015Albert et al, , 2016Klugel et al, 2015). These intermediate reservoir zones, which will normally be located at rheological or structural discontinuities inside the lithosphere, do not need to be stable or permanent along the whole history of the volcanic field.…”
Section: Sheet Intrusions and Magma Overpressurementioning
confidence: 97%